Two-point fixation enhanced the outcome of laparoscopy-assisted ventriculoperitoneal shunt in adult patients with hydrocephalus: a retrospective study - Wu, Jing-Nan; Zhou, Yu-Jie; Wang, Lei; Gan, Jin-Lu; Wang, Jian; Zhao, Hong-Yang; Lei, De-Qiang (Frontiers in Surgery, 2023)
Objective: In patients with hydrocephalus, laparoscopy significantly improved ventriculoperitoneal shunt (VPS) outcomes. However, abdominal complications still occur, which require revision surgeries. In this study, we aimed to examine whether laparoscopy-assisted VPS with two-point fixation (LAVPS-TPF) has better outcomes than VPS (open-VPS) and laparoscopy-assisted VPS with no fixation (LAVPS-NF). Methods: Clinical records of 105 open-VPS, 40 LAVPS-NF, and 49 LAVPS-TPF from 2015 to 2020 were retrospectively reviewed. Data including body mass index (BMI), etiology, abdominal surgery history, Glasgow coma scale (GCS), operation time, in-hospital days, shunt failure, complications, and modified Rankin scores (mRS) were analyzed including subgroups of patients with history of abdominal surgery, GCS scores and revision surgeries. Results: LAVPS-TPF demonstrated decreased shunt failure rates at 12 months (2.04%) compared to open-VPS group (14.29%, P = 0.020), and reduced abdominal shunt-related complications (P = 0.004 vs. open-VPS and LAVPS-NF) and shunt revisions. In patients with an abdominal history (n = 51), 12-month shunt failure rates (P = 0.020 vs. open-VS), repairment frequency (P = 0.020 vs open-VS), and abdominal complications (P = 0.003 and 0.006 vs open-VS and LAVPS-NF) were reduced in the LAVPS-TPF group. In patients with GCS 13~15 (n = 152), shunt failure rates at 12 months, abdominal complications and revision frequency were decreased in LAVPS-TPF group (P < 0.05 vs other groups). Compared to LAVPS-NF group, neurological complications were decreased too (P = 0.001). Among revision surgeries (n = 28), fixed shunts resulted in improved shunt survival rates at 12 months, reduced abdominal complications and secondary revisions (P < 0.05). Moreover, a more optimal recovery without neurological sequelae was achieved by shunt fixation than LAVPS-NF (P < 0.01). Conclusions: LAVPS-TPF significantly improved shunt survival rates at 12 months and reduced the incidence of abdominal shunt-related complications compared to open-VPS and LAVPS-NF, especially in patients with history of abdominal surgery, higher GCS scores, and revision surgeries. However, further studies are required to confirm these benefits.